Preparation method of alumina-zirconia composite ceramic constant-temperature water mixing valve
By preparing alumina-zirconia composite ceramic materials, the problems of rapid wear, easy corrosion, and high processing difficulty of metal thermostatic mixing valves have been solved, realizing a ceramic thermostatic mixing valve with high hardness, corrosion resistance, and low cost, which has long service life and high-precision temperature control capabilities.
Patent Information
- Application Number
- CN202511401278.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-28
- Publication Date
- 2026-01-27
AI Technical Summary
Existing metal thermostatic mixing valves suffer from rapid wear, easy corrosion, difficult processing, high cost, and environmental problems, making it difficult to meet the requirements for long service life and high precision.
A high-hardness, corrosion-resistant ceramic thermostatic mixing valve was prepared by using alumina-zirconia composite ceramic materials. The process involved mixing alumina sol and zirconia sol, followed by hydrothermal crystallization, calcination, spray drying, and injection molding.
It achieves extremely high hardness and corrosion resistance, significantly extends service life, reduces production costs, maintains the accuracy and sensitivity of temperature control, and solves the defects of metal valve bodies.
Smart Images

Figure CN121405441A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermostatic mixing valve technology, specifically a method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve. Background Technology
[0002] Thermostatic mixing valves are key components of heating systems, widely used in electric water heaters, solar water heaters, and centralized hot water supply systems. Their main function is to allow users to adjust the mixing temperature of hot and cold water as needed, and quickly stabilize it at the set temperature, ensuring a constant outlet water temperature unaffected by changes in water temperature, flow rate, or water pressure, effectively solving the problem of fluctuating water temperature during bathing. Furthermore, when the cold water supply is interrupted, the mixing valve can quickly and automatically shut off the hot water, providing a safety protection function.
[0003] Currently, the vast majority of thermostatic mixing valves on the market are made of metal, with low-end products using easily machinable brass and high-end products using 316 stainless steel. However, metal materials have the following significant drawbacks:
[0004] Particulate impurities in the water (such as sand and iron filings) can easily enter the gap between the valve core and the valve sleeve, causing severe wear during the reciprocating motion adjustment of the valve core, resulting in a significant shortening of the product life.
[0005] Metal materials are susceptible to corrosion, and scale and impurities easily accumulate on their surfaces, affecting the accuracy of temperature control and, in severe cases, even causing valves to jam and fail.
[0006] Brass contains heavy metals and is not environmentally friendly; while stainless steel is difficult to process, time-consuming, and costly.
[0007] Therefore, there is an urgent need to develop a non-metallic thermostatic mixing valve that combines high hardness, high toughness, corrosion resistance, dirt resistance, and long service life to overcome the inherent defects of existing metal valve bodies. Summary of the Invention
[0008] The purpose of this invention is to provide a method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve to solve the problems in the prior art.
[0009] To achieve the above objectives, the present invention provides the following technical solution: The present invention provides a method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve, comprising the following steps:
[0010] (a) Preparation of alumina sol A: AlCl3·6H2O was prepared into an aqueous solution, dispersant PEG4000 was added, and after stirring evenly, ammonia was added dropwise until pH=9-10 to form sol A;
[0011] (b) Preparation of zirconia sol B: Prepare an aqueous solution of ZrOCl2·8H2O, add cerium nitrate, magnesium nitrate, dysprosium nitrate and samarium nitrate, stir evenly and then add ammonia water dropwise until pH=9-10 to form sol B;
[0012] (c) Mixing and processing: Mix sol A and sol B, wash and filter, add ethanol, stir, rinse and freeze dry to obtain composite ceramic gel;
[0013] (d) Hydrothermal crystallization: The obtained gel is placed in a high-pressure reactor and hydrothermally reacted at 120-200℃ and 1-3MPa for 10-30 hours to obtain the original crystal powder, which is then calcined at 500-800℃ to remove the bound water.
[0014] (e) Batching and grinding: Fumed silica, BaSi2N2O2 and BaTiO3 are added to the calcined powder, and the composite ceramic slurry is obtained by grinding with a sand mill.
[0015] (f) Spray drying and modification: The slurry is spray dried and oleic acid is added in hot air for surface modification to obtain modified powder;
[0016] (g) Internal mixing to prepare feed: The modified powder and the components of the organic binder are mixed in an internal mixer to prepare ceramic feed;
[0017] (h) Injection molding: The feed material is injected into the mold to form a green body;
[0018] (i) Degreasing and sintering: After the green body is degreased by stage heating, it is heated to 1500℃ and then cooled to 1380℃ in a high-temperature sintering furnace and held for 10 to 15 hours to complete sintering;
[0019] (j) Machining and polishing: The sintered body is precision machined and the mating surfaces are polished to obtain the thermostatic mixing valve.
[0020] Preferably, the amount of PEG4000 added in step (a) is 0.1% to 0.5% of the mass of AlCl3·6H2O.
[0021] Preferably, in step (b), the amount of cerium nitrate added is 0.5–1 mol of ZrOCl2·8H2O, the amount of magnesium nitrate added is 0.5–1 mol, the amount of dysprosium nitrate added is 0.2–0.8 mol, and the amount of samarium nitrate added is 0.3–0.5 mol.
[0022] Preferably, in step (e), the amount of fumed silica added is 0.2% to 1% of the powder mass, the amount of BaSi2N2O2 added is 0.05% to 0.2%, and the amount of BaTiO3 added is 1% to 5%.
[0023] Preferably, the amount of oleic acid added in step (f) is 0.1% to 1% of the powder mass.
[0024] Preferably, the organic binder in step (g) comprises, by mass percentage: 40%–50% paraffin wax, 5%–10% carnauba wax, 10%–20% methacrylic acid resin, 10%–20% low molecular weight polyoxymethylene, 10%–20% syndiotactic polypropylene, 1%–5% behenic acid, and 1%–5% S-80.
[0025] Preferably, the heating program for the defatting stage in step (i) is as follows: from room temperature to 100°C at a rate of 2 to 5°C / minute, from 100 to 250°C at a rate of 0.5 to 2°C / minute, from 250 to 450°C at a rate of 1 to 2°C / minute, and from 450 to 750°C at a rate of 3 to 5°C / minute.
[0026] A thermostatic mixing valve is prepared by the above method.
[0027] The present invention has at least the following beneficial effects:
[0028] (1) This method uses an alumina-zirconia composite ceramic material, whose hardness (Hv can reach over 1850) is much higher than that of traditional brass (Hv ~ 120) and stainless steel (Hv ~ 200) valve bodies. The extremely high hardness enables the valve core and valve sleeve to exhibit extremely strong wear resistance when facing hard particulate impurities in the water flow. Experimental data shows that the service life of the product of this invention (greater than 180,000 times) far exceeds that of the brass valve body (about 20,000 times) and stainless steel valve body (about 80,000 times) in the comparative example, with the service life increased several times. This solves the fatal defect of short valve life caused by wear in the background technology and has good application prospects.
[0029] (2) Ceramic materials have natural chemical inertness and are resistant to acid and alkali corrosion, fundamentally eliminating the problem of metal valve bodies being easily corroded and rusted. At the same time, by adding components such as BaSi2N2O2, the morphology of ceramic grains is controlled to make them smooth, reducing the number of angular grains at the microscopic level, thereby greatly reducing the possibility of surface deposits of scale and impurities, ensuring the accuracy of temperature control and the sensitivity of action of the valve after long-term operation, and avoiding the risk of failure due to corrosion or dirt jamming.
[0030] (3) Although ceramic materials have excellent properties, this invention uses optimized injection molding (CIM) technology for mass production, which overcomes the disadvantages of traditional ceramic processing methods (such as grinding) such as low efficiency, high cost and limited shape. It achieves near-net-shape forming of complex ceramic valve bodies in one go, and only a small amount of precision processing is required afterward, which greatly reduces production costs and dependence on skilled workers. It achieves high performance while also being economical. Attached Figure Description
[0031] Figure 1 The method flowchart provided by the present invention. Detailed Implementation
[0032] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "and / or" as used in this specification includes any and all combinations of one or more of the associated listed items.
[0033] Example 1
[0034] Figure 1 A flowchart provided for an embodiment of the present invention. In this embodiment, as... Figure 1 As shown, a method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve may include the following steps:
[0035] S1. Preparation of alumina sol A: Prepare an aqueous solution with a concentration of 0.5 mol / L by dissolving 1.5 mol of analytical grade AlCl3·6H2O, and add 0.2% of its mass of PEG4000 as a dispersant. After stirring evenly, add ammonia water (NH3·H2O) dropwise at a rate of 2 ml / min while stirring continuously until the pH value of the solution reaches 9, thus forming sol A.
[0036] S2. Preparation of Zirconia Sol B: Prepare an aqueous solution of 0.15 mol ZrOCl2·8H2O with a concentration of 0.5 mol / L. Then add cerium nitrate (1 mol% of ZrOCl2·8H2O), magnesium nitrate (0.5 mol%), dysprosium nitrate (0.8 mol%), and samarium nitrate (0.3 mol%). After stirring evenly, add ammonia water dropwise at a rate of 2 ml / min while stirring continuously until the pH of the solution reaches 9, thus forming sol B.
[0037] S3. Mixing and gel treatment: Mix sol A and sol B, stir thoroughly, and then wash with deionized water multiple times to remove chloride ions (Cl-). After filtration, add analytical grade anhydrous ethanol, stir at high speed, wash multiple times, and then freeze-dry to obtain a composite ceramic gel mixture.
[0038] S4. Hydrothermal Crystallization and Calcination: The freeze-dried gel was placed in a high-pressure reactor and subjected to a hydrothermal reaction at 120°C and 1 MPa for 10 hours to crystallize the amorphous metal hydroxide gel, forming flocculent porous ceramic precursors with a grain size of approximately 0.15 micrometers. The resulting precursors were then calcined at 500°C to remove bound water.
[0039] S5. Batching and Grinding: Add 0.2% fumed silica, 0.05% BaSi2N2O2 and 5% BaTiO3 by weight of the calcined original crystal powder, and grind and mix them in a sand mill to obtain a uniform composite ceramic powder slurry.
[0040] S6. Spray Drying and Surface Modification: The prepared composite ceramic slurry is spray dried. During spray drying, 0.1% oleic acid by weight of the powder is mixed into the hot air, so that the surface of the dried powder particles is coated with a thin film of oleic acid, thus performing surface modification.
[0041] S7. Internal mixing feed: The modified powder is put into an internal mixer, and organic binder components are added according to the following mass percentages: paraffin wax 50%, palm wax 5%, methacrylic resin 10%, low molecular weight polyoxymethylene 10%, syndiotactic polypropylene 10%, behenic acid 5%, S-80 5%. The mixture is mixed evenly to make ceramic injection molding feed.
[0042] S8. Injection Molding: The prepared ceramic feedstock is placed into a ceramic injection molding machine, and the mixing valve green body is obtained by injection molding using a constant temperature mixing valve mold.
[0043] S9. Degreasing: Place the formed green body into a degreasing furnace to remove the organic binder. The degreasing heating program is as follows: room temperature to 100℃, heating rate 2℃ / min; 100℃ to 250℃, heating rate 0.5℃ / min; 250℃ to 450℃, heating rate 1℃ / min; 450℃ to 750℃, heating rate 3℃ / min.
[0044] S10. Sintering: The degreased green body is placed in a high-temperature sintering furnace for sintering. The sintering temperature rise curve is as follows: room temperature to 1000℃, heating rate 5℃ / min; 1000℃ to 1500℃, heating rate 5℃ / min; 1500℃ to 1380℃, cooling rate 20℃ / min; holding at 1380℃ for 10 hours, and then naturally cooling to room temperature.
[0045] S11. Precision machining and polishing: The sintered ceramic blank is precision machined to ensure dimensional accuracy. Then, the mating surfaces of the valve core and valve sleeve are polished to achieve the required sealing effect.
[0046] Example 2
[0047] A method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve, the steps of which are basically the same as those in Example 1, the difference being in the process parameters:
[0048] In S1, the amount of PEG4000 added is 0.5% of the mass of AlCl3·6H2O, and ammonia water is added dropwise until pH=10.
[0049] In S2, the additives added are: 0.5 mol% cerium nitrate, 0.5 mol% magnesium nitrate, 0.5 mol% dysprosium nitrate, and 0.5 mol% samarium nitrate, and ammonia water is added dropwise until pH = 10.
[0050] In S4, the hydrothermal reaction conditions are 200℃, 3MPa, and 30 hours, resulting in near-spherical primary crystals with a grain size of approximately 0.8 micrometers. The calcination temperature is 800℃.
[0051] In S5, the additive amounts are: 1% fumed silica, 0.2% BaSi2N2O2, and 3% BaTiO3.
[0052] In S6, the amount of oleic acid added is 1% of the powder mass.
[0053] In S7, the organic binder composition is as follows: paraffin wax 40%, palm wax 10%, methacrylic resin 20%, low molecular weight polyoxymethylene 5%, syndiotactic polypropylene 20%, behenic acid 2%, and S-801.
[0054] S9 degreasing program: room temperature to 100℃ (5℃ / min), 100-250℃ (2℃ / min), 250-450℃ (2℃ / min), 450-750℃ (5℃ / min).
[0055] S10 sintering procedure: room temperature to 1000℃ (1℃ / min), 1000-1500℃ (3℃ / min), 1500-1380℃ (50℃ / min), 1380℃ for 15 hours.
[0056] Example 3
[0057] A method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve, the steps of which are basically the same as those in Example 1, the difference being in the process parameters:
[0058] In S1, the amount of PEG4000 added is 0.3% of the mass of AlCl3·6H2O, and ammonia water is added dropwise until pH=9.5.
[0059] In S2, the amount of additives added is 0.5 mol%, and ammonia water is added dropwise until pH = 9.5.
[0060] In S4, the hydrothermal reaction conditions were 160℃, 2.4MPa, and 24 hours, resulting in polygonal primary crystals with a grain size of approximately 0.4 micrometers. The calcination temperature was 600℃.
[0061] In S5, the additive amounts are: 0.5% fumed silica, 0.1% BaSi2N2O2, and 3.5% BaTiO3.
[0062] In S6, the amount of oleic acid added is 0.8% of the powder mass.
[0063] In S7, the organic binder composition is as follows: paraffin wax 45%, palm wax 7%, methacrylic resin 15%, low molecular weight polyoxymethylene 15%, syndiotactic polypropylene 12%, behenic acid 2%, and S-802.
[0064] S9 degreasing program: room temperature to 100℃ (3℃ / min), 100-250℃ (1℃ / min), 250-450℃ (1.5℃ / min), 450-750℃ (3.5℃ / min).
[0065] S10 sintering procedure: room temperature to 1000℃ (2.5℃ / min), 1000-1500℃ (3.5℃ / min), 1500-1380℃ (40℃ / min), 1380℃ for 12 hours.
[0066] Comparative Example 1 uses 316 stainless steel to prepare a thermostatic mixing valve through machining.
[0067] Comparative Example 2 uses brass material to prepare a thermostatic mixing valve through machining.
[0068] The performance of the thermostatic mixing valves prepared in Examples 1-3 and Comparative Examples 1-2 was tested, and the results are shown in the table below:
[0069]
[0070] As shown in the table above, the alumina-zirconia composite ceramic thermostatic mixing valves prepared in Examples 1-3 of this invention are significantly superior to the conventional metal valve bodies in the comparative examples in terms of hardness, bending strength, corrosion resistance, and service life, while also having the advantage of low processing cost.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; under the concept of the present invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of the present invention as described above, which are not provided in detail for the sake of brevity; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve, characterized in that, Includes the following steps: (a) Preparation of alumina sol A: AlCl3·6H2O was prepared into an aqueous solution, dispersant PEG4000 was added, and after stirring evenly, ammonia was added dropwise until pH=9-10 to form sol A; (b) Preparation of zirconia sol B: Prepare an aqueous solution of ZrOCl2·8H2O, add cerium nitrate, magnesium nitrate, dysprosium nitrate and samarium nitrate, stir evenly and then add ammonia water dropwise until pH=9-10 to form sol B; (c) Mixing and processing: Mix sol A and sol B, wash and filter, add ethanol, stir, rinse and freeze dry to obtain composite ceramic gel; (d) Hydrothermal crystallization: The obtained gel is placed in a high-pressure reactor and hydrothermally reacted at 120-200℃ and 1-3MPa for 10-30 hours to obtain the original crystal powder, which is then calcined at 500-800℃ to remove the bound water. (e) Batching and grinding: Fumed silica, BaSi2N2O2 and BaTiO3 are added to the calcined powder, and the composite ceramic slurry is obtained by grinding with a sand mill. (f) Spray drying and modification: The slurry is spray dried and oleic acid is added in hot air for surface modification to obtain modified powder; (g) Internal mixing to prepare feed: The modified powder and the components of the organic binder are mixed in an internal mixer to prepare ceramic feed; (h) Injection molding: The feed material is injected into the mold to form a green body; (i) Degreasing and sintering: After the green body is degreased by stage heating, it is heated to 1500℃ and then cooled to 1380℃ in a high-temperature sintering furnace and held for 10 to 15 hours to complete sintering; (j) Machining and polishing: The sintered body is precision machined and the mating surfaces are polished to obtain the thermostatic mixing valve.
2. The method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve according to claim 1, characterized in that, The amount of PEG4000 added in step (a) is 0.1% to 0.5% of the mass of AlCl3·6H2O.
3. The method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve according to claim 1, characterized in that, In step (b), the amount of cerium nitrate added is 0.5–1 mol of ZrOCl2·8H2O, the amount of magnesium nitrate added is 0.5–1 mol, the amount of dysprosium nitrate added is 0.2–0.8 mol, and the amount of samarium nitrate added is 0.3–0.5 mol.
4. The method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve according to claim 1, characterized in that, In step (e), the amount of fumed silica added is 0.2% to 1% of the powder mass, the amount of BaSi2N2O2 added is 0.05% to 0.2%, and the amount of BaTiO3 added is 1% to 5%.
5. The method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve according to claim 1, characterized in that, The amount of oleic acid added in step (f) is 0.1% to 1% of the powder mass.
6. The method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve according to claim 1, characterized in that, The organic binder mentioned in step (g) comprises, by mass percentage: 40%–50% paraffin wax, 5%–10% carnauba wax, 10%–20% methacrylic acid resin, 10%–20% low molecular weight polyoxymethylene, 10%–20% syndiotactic polypropylene, 1%–5% behenic acid, and 1%–5% S-80.
7. The method for preparing an alumina-zirconia composite ceramic thermostatic mixing valve according to claim 1, characterized in that, The heating program for the defatting stage in step (i) is as follows: from room temperature to 100°C at a rate of 2–5°C / minute, from 100 to 250°C at a rate of 0.5–2°C / minute, from 250 to 450°C at a rate of 1–2°C / minute, and from 450 to 750°C at a rate of 3–5°C / minute.
8. A thermostatic mixing valve, characterized in that: Prepared by the method described in any one of claims 1 to 7.